Literature Review: Analysis of the Relationship between Employer Branding, Employee Engagement, and Employee Retention - Mustika (Nomico, 2024)
Employer branding is an essential concept that significantly influences employees' perceptions and experiences within an organization, ultimately affecting employee retention and engagement. This research aims to explore the importance of employer branding by employing a Systematic Literature Review (SLR) methodology, analyzing a diverse range of academic sources from reputable databases, including Scopus, Emerald, and Google Scholar. The inclusion criteria focused on open-access journals published in both English and Indonesian, ensuring a comprehensive understanding of the topic. The findings indicate a strong correlation between effective employer branding and increased employee retention rates. Employees are more likely to remain with organizations that present a positive brand image, showcasing a strong cultural identity and aligning with their values. Furthermore, the study highlights the significance of emotional factors, particularly employee engagement, in influencing retention. Engaged employees tend to be more productive and committed to their work, fostering a sense of belonging and loyalty to the organization. These insights underscore the necessity for companies to invest in employer branding strategies, as a well-defined employer brand not only attracts top talent but also retains valuable employees. By prioritizing employer branding, organizations can enhance workforce stability and overall performance, ultimately leading to a more motivated and dedicated workforce that drives success.